Mechanistic investigations of phase behavior in Eudragit (R) blends - Menjoge, Anupa R.; Kulkarni, M. G. (International Journal of Pharmaceutics, 2007)
Blends of Eudragit (R) E (EE) and polymeric excipients using thermal analysis and FTIR spectroscopy were examined. The interactions amongst the blend components were quantified in terms of parameters K-1 and K-2 in Schneider equation and were explained on the basis of interactions between the functional groups of the blend constituents investigated by FTIR spectroscopy. EE formed miscible blends with EC and polyelectrolyte complexes increasing in strength in the order: ES < HPMCP < CAP < EL. From the T-g data the weight fraction of EE in the polyelectrolyte complex was determined. The importance of formulating polyelectrolyte complexes in stoichiometric ratios has been highlighted. The duration over which the release can be sustained by polyelectrolyte complexes has been correlated with equilibrium swelling of the polyelectrolyte complex and parameter K, for the first time. This would help in the choice of blend constituents and composition to tailor drug release. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: degree of swelling; Glass transition temperature; miscibility; polyelectrolyte complex; polymer blends; polymer-polymer interactions